Bioabsorbable device to prepare subcutaneous pockets for islet transplantation. Issue 4 (5th September 2018) - Kuwabara, Rei; Iwata, Hiroo
Abstract : Small invasive transplantation of islets and long maintenance of the islet graft without immunosuppression has been studied for the treatment of type 1 diabetes. Clinically, subcutaneous pockets surrounding vascular‐rich tissue are prepared for islet transplantation using a device made of the materials. Here, gelatin sheets were implanted into two dorsal subcutaneous sites in diabetic ACI rats, and a mixture of bFGF and sodium hyaluronate solution was injected around the gelatin sheets. A total of 1500 islets isolated from F344 rats were transplanted into each of the pockets 7 days after injection of the bFGF mixture. Nine of 10 diabetic ACI rats with allogeneic islet graft demonstrated long‐term normoglycemia without administration of immunosuppressant. Gelatin sheets almost disappeared 67 days after implantation. Thus, subcutaneous immune‐tolerant sites can be prepared using gelatin sheets and a sodium hyaluronate–bFGF mixture. Allogeneic islets transplanted into the sites can survive and control blood glucose levels for a long period, even without immunosuppression. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1107–1112, 2019.